Analisis Tipologi Sains dan Agama serta Relevansinya dengan Upaya Perguruan Tinggi Keagamaan Islam dalam Mengembangkan Sains Islam - Aisyah Nur Afifah (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2023)
This research aims to analyze and describe the relationship between science and religion, which remains a subject of discussion and debate among experts worldwide. It is a library research study with primary sources consisting of books written by Ian Barbour and Zakir Naik. The approach used is qualitative descriptive with content analysis method. The research has found that Ian Barbour's thoughts on the connection between religion and science can indeed be considered as reliable references. On the other hand, Zakir Naik's ideas regarding science and religion lean towards objectively proving various natural phenomena based on the Qur'an as a divine revelation. Not only Ian Barbour and Zakir Naik, but various other figures also contribute to supporting the argument that there is no gap between science and religion. In Indonesia, a program has been promoted to address the separation between knowledge and religion, which involves integrating science and knowledge while developing Islamic science in religious discussions. This is achieved through the use of Islamic Higher Education Institutions (PTKI) as a means of realization, such as increasing research activities for faculty and students, implementing teaching methods that encourage critical thinking among students, and improving curricula that support the development of Islamic science on campuses.